(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Using perfluorocarbon liquid (PFCL) for short-term tamponade of the vitreous cavity expands the indications to surgical treatment of retinal detachment (RD) of various genesis. However, the question about affecting action of PFCL and about the maximal safe term of tamponade is still open. The purpose of the present paper was to determine the characteristics of the effect of two week PFCL tamponade on the bioelectrical functional activity in the rabbit’s retina and to compare the action of PFCL and light silicone oil (SO) with viscosity of 5 700 cSt in dynamics by electroretinography (ERG) at different time points after tamponade (7, 14 and 30 days). Material and Methods. The experiment involved 6 male rabbits (12 eyes). Each animal was performed vitrectomy following 14 day tamponade with PFCL (in the right eye) and light SO. ERG was performed at baseline as well as after tamponade removal at time points of 7, 14 and 30 days. Results. 14 day PFCL (perfluorodecalin) tamponade of the rabbit eyes induced similar bioelectric reaction in the retina, comparing to light SO tamponade (viscosity 5 700 sST). The reaction consisted of increased activity in photoreceptor and inner retinal layers at early terms and normalization of retinal functions at late terms (1 month) after tamponade removing with a decrease in inner layer reactivity. Conclusion. PFCL can be considered as a short-term tamponade agent.